TINJAUAN KEKUATAN PEMBUKTIAN KETERANGAN SAKSI YANG TIDAK DISUMPAH KARENA KETERBELAKANGAN MENTAL DALAM PEMERIKSAAN PERKARA KEKERASAN SEKSUAL (Studi Putusan Pengadilan Negeri Lubuk Basung Nomor : 104/Pid.B/2013/PN.LB.BS) - Bagas Pradikta Haryanto, Sindura Debri Walanti (GEMA, 2015)
This study aims to determine whether the provision of statements of witnesses who are not sworn as clicking natural mental retardation is not contrary to the KUHAP and how the attitude of the judges in considering the testimony of witnesses who are not sworn as mentally retarded to decide cases of sexual violence in the Lubuk Basung First Instance Court. This research includes the study of normative law with prescriptive nature. The approach used by the researchers is a case study. Source of data used in the writing of this law is the secondary data, which use materials that can be ruling literature, legislation, documents, books, and literature related to the problem under study. Technical analysis is a method of data used by the pattern of thinking deductive syllogism. Based on this study we concluded that the witness testimony given by witnesses with mental retardation with no sworn not contradict or are in accordance with the provisions of the KUHAP. Probative value attached to the sworn testimony of the witnesses who are not able to strengthen the confidence of Judges and can be used as a guide for an additional judge and as valid evidence, as long as the information is in accordance with other valid evidence.